The Role of Applying Educational Investment and its Impact in Attracting External Funding and Increasing the Effectiveness of the Budget for Higher Education Institutions - Asaad Mansour Al-Quraishi; Haider Abbas Al-Attar; Rashid Bani Shannan (Journal of Madenat Alelem University College, 2020)
The research aims to highlight the extent to which educational investment can be used to attract funding from outside the budget of higher education institutions through the transition from central to mixed financial support (part of the budget is partially independent) by funding activities. The acquisition and disbursement of funds became a new mechanism adopted in the countries of the world, which will be the best solution for the welfare of material in universities. In order to achieve the objectives of the study, the researchers used the descriptive analytical method by preparing the questionnaire list prepared scientifically by some professors of the Faculty of Management and Economics at Al-Muthanna University. This questionnaire was distributed to some employees at Al-Muthanna University In the College of Management and Economics, the directors of the scientific and administrative departments at the university presidency, in addition to the accountants and auditors at the University of Muthanna. 75 forms were distributed and 70 samples were retrieved (93%). Statistical analyzes were conducted to achieve hypotheses to study, Therefore, the researchers reached a number of conclusions. The most important of which is the absence of a systematic framework within the state’s financial policy to regulate the investment process and the insufficient level of financial planning in the preparation of the general budget for investment financing, which caused the lack of continuous funding for public investment programs. The financial policy of the state, especially in the issue of investment and the preparation of a strategic plan within the general budget to support the investment process from the establishment of investment funds within all government sectors or funds within the local administrations of the provinces to support investment there.